Enhancing condensation with micro/nanostructured metal additively manufactured materials - Foo, Ru Yuan (Nanyang Technological University, 2023)
This report examines the dropwise condensation heat transfer performance on additively manufactured micro/nanostructured materials. Multiple studies have been conducted on surface structures, which has garnered growing interest owing to its distinct characteristics. In this project, the behaviour of water condensation on different enhanced surfaces and in the presence of surface coating has been investigated in relation to surface morphology, wettability, and heat transfer performance.